Acute Toxicity Studies and Evaluation of Analgesic Property of the Methanol Stem Bark Extract of Neocarya macrophylla - A.J. Yusuf, M.I. Abdullahi, A.K. Haruna, A.M. Musa, Z.Y.Y. Ibrahim, A. Uba (Journal of Applied Pharmaceutical Science, 2015)
The methanol stem bark extract of Neocarya macrophylla was screened for its analgesic activity using acetic acid-induced writhing in mice and formalin-induced pain in rats. The results of the study showed that the extract (60mg/kg, i.p.) decreased writhing response with 63.9% inhibition. The methanol extract also exhibited significant analgesic effect (P
Keywords: Neocarya macrophylla,extract,formalin,acetic acid and analgesic models.